A Qualitative Analysis of the Optimal Discharge Summary: Effective Communication of Medication Changes for Older Patients. (May 2023) - Komenan, Ked; Bouveret, Perrine; Delecluse, Céline; Robinet, Pierre; Puisieux, François; Visade, Fabien
Background: The importance of the discharge summary (DS) is well recognized. The format to be used is also important, but this aspect has not yet been studied in the literature. The purpose of this work was to establish a DS format for older patients that ensures effective communication with general practitioners (GPs).Methods: This study was based on the grounded theory approach to qualitative analysis. Data was collected from GPs during semi-structured and directive interviews.Results: Semi-structured interviews were conducted with 12 GPs and directive interviews with 39 GPs. A consensus was reached on one DS version providing selected information items such as trends in laboratory results (rising/falling) and information about planned drug withdrawals or specialist consultations.Conclusion: This work led to a consensus on the most appropriate format for the DS for older patients returning home. Its use in routine practice is needed to confirm its reception by GPs.